METHODS OF USING EDUCATIONAL MATERIALS IN NATURAL LANGUAGE LESSONS IN PRIMARY SCHOOLS - Ilyasova, Zamira Uzakbaevna; Sarieva, Munira Ramatillaevna (SCIENCE and SOCIETY, 2026)
The article discusses methods of using learning materials in mother tongue lessons in primary school. It analyzes the effective selection of educational materials, their application based on pedagogical technologies, and increasing students’ cognitive activity through interactive and didactic methods. Special attention is given to the systematic and consistent organization of learning materials considering students’ age and individual characteristics.